Unleashing the Artist Within: New Directions for Research in Adult Education - Randee Lipson Lawrence; Craig A. Mealman (Adult Education Research Conference, 2000)
The potential for using various art forms (drama, poetry, music, literature, visual art) in the collection and analysis of data, and in the expression of research findings is explored in this roundtable discussion.